Frequency of MRI-detected peripheral osteoarthritis in athletes during the Summer Olympics in Rio 2016. Issue 4 (December 2021) - Merritt, Alexander; Roemer, Frank W.; Heiss, Rafael; Jarraya, Mohamed; Guermazi, Dorra; Hayashi, Daichi; Engebretsen, Lars; Crema, Michel D.; Guermazi, Ali
Abstract: Objective: To describe the frequency and severity of magnetic resonance imaging (MRI) based peripheral osteoarthritis (OA) in athletes during the Rio de Janeiro 2016 Olympic Games. Methods: All MRIs of the peripheral joints in Olympic athletes, performed at the centralized imaging facility, either following acute trauma or for non-traumatic joint pain, were included. All MRIs were retrospectively reviewed for presence and severity of MRI-based OA using an adapted Outerbridge classification for cartilage and adapted classifications for other tissues. Scoring of MRI abnormalities was independently and retrospectively performed without reference to the on-site clinical reports. The frequencies of MRI-detected OA were tabulated and grouped into sports categories, athletes' age (<25; 25–29; and ≥30 years of age), and sex. Results: 11, 274 athletes participated in the Games. 320 athletes underwent MRI of the peripheral joints. One hundred sixty (50.0%) were female, 109 (34.1%) were <25 years, 132 (41.3%) between the ages of 25 and 29 years old, and 79 (24.7%) ≥30 years old. 53 (16.6%) had MRI-based OA, with slightly more than half having severe OA. In every age category, severe OA was the most frequent finding and there was a linear trend for increased likelihood of having OA with increasing age (Cochran-Armitage test, p ​= ​0.009). Frequencies of OA were similar in male and female athletes. The wrist (29.2%) and the knee (23.3%) were the most commonly affected joints. Conclusions: MRI-defined OA was not uncommon among elite athletes in this selected sample.